Evaluation of Phenolic Phytochemical Enriched Commercial Plant Extracts on the In Vitro Inhibition of α-Glucosidase - Brown, Allie; Anderson, Danielle; Racicot, Kenneth; Pilkenton, Sarah J.; Apostolidis, Emmanouil (Frontiers in Nutrition, 2017)
Green tea (GT), cranberry (CR), and tart cherry extracts were evaluated for their ability to inhibit yeast α-glucosidase, relevant to glucose uptake. The total phenolic content (TPC), antioxidant activity, and in vitro inhibitory activity of yeast α-glucosidase were examined for the extracts in the present study. GT had higher TPC and antioxidant activity, but CR demonstrated a greater α-glucosidase inhibitory activity, on phenolic basis. CR was fractionated using LH-20 column chromatography into two fractions: 30% methanol (CME) and 70% acetone (CAE). TPC, antioxidant activity, and yeast α-glucosidase inhibitory activity were determined for the fractions. CAE had a greater TPC and antioxidant activity than CME, but the two fractions had a synergistic effect when inhibiting yeast α-glucosidase. Our findings suggest that CR has the greatest potential to possibly manage post-prandial blood glucose levels via the inhibition of α-glucosidase, and that the effect is through synergistic activity of the extract’s phenolic compounds.